2010
DOI: 10.1177/0899764010378357
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Constraints on Nonprofit Leadership Tactics in Times of Recession

Abstract: The impact of the global recession has served to increase resource pressures on voluntary organizations in many social service sectors, serving to constrain the choices that organizational leaders can make in the face of changing resource niches. Not all organizational leaders face the same set of viable choices in the face of both changing demands from funding bodies and highly dynamic resource niches. Drawing on theories of organizational change, it is possible to identify three key factors that will serve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…A prevalent view of NFP reserves is that they are accumulated for a ‘rainy day’ (PwC : 18), and that boards strategically accumulate reserves at times when organisational inputs are in excess of those needed for outputs, with the object of using them for mission‐related activities in the future when external events, such as a recession, or changes in funding occur (Moses ; Feenstra and van Helden ; Bowman ; Bradley et al. ; Never ). However, this is not the only motivation for reserves accumulation.…”
mentioning
confidence: 99%
“…A prevalent view of NFP reserves is that they are accumulated for a ‘rainy day’ (PwC : 18), and that boards strategically accumulate reserves at times when organisational inputs are in excess of those needed for outputs, with the object of using them for mission‐related activities in the future when external events, such as a recession, or changes in funding occur (Moses ; Feenstra and van Helden ; Bowman ; Bradley et al. ; Never ). However, this is not the only motivation for reserves accumulation.…”
mentioning
confidence: 99%
“…Calabrese ( 2013 ) found that 40 % of nonprofi t organizations had no operating reserves and that the median held only 1 month of operating expenditures in reserves. Faced with a sudden and rapid escalation of demand and profound cuts in funding from all sources, many organizations have had to respond with cost-cutting measures to mitigate their diminished funds (Harrison et al 2011 ;Morreale 2011 ;Mosley et al 2012 ;Never 2010 ). These types of measures are costly in terms of negative impacts for the individuals seeking help and for the organization's ongoing capacity.…”
Section: Resultsmentioning
confidence: 99%
“…To cope, fi scally pressured nonprofi ts have had to make choices to, essentially, either increase revenue or cut costs in a number of ways. According to recent surveys, nonprofi ts report simultaneously using a range of coping strategies, including: launching new fundraising efforts, drawing on reserves, cutting administrative costs, instituting salary freezes, postponing new hires, relying more on volunteers, increasing marketing and advocacy activity, reducing program services, and creating collaborative relationships among others (Boris et al 2010 ;Bridgeland et al 2009 ;Golensky and Mulder 2006 ;Harrison et al 2011 ;Mosley et al 2012 ;Never 2010 ;Salamon et al 2009 ). If human service organizations are able to maintain service levels through an economic downturn through the use of stopgap measures other than reserve funds, it calls into question the necessity to build reserves for organization resilience.…”
Section: Budget Balancing Strategies In the 2007-2009 Recessionmentioning
confidence: 99%
“…In the existing academic and practitioner literature on leadership in the third sector, there is extensive research on what those in leadership positions actually do, for example: governance (Jegers, 2009;Taylor, 2015); strategising (Never, 2010;Hopkins et al, 2014); and managing human resource (Kreutzer et al, 2009). In addition, there is research into: leadership models (Dwyer et al, 2013;Boerner and Geber, 2012;and Mahalinga Shiva and Suar, 2012); team member exchange (Willems, 2015); leadership philosophies (De Vita, 2008;Parris and Peachey, 2012;and Ebener and O'Connell, 2010); and distributed leadership (Duncan and Schoor, 2015).…”
Section: Leadership In the Third Sectormentioning
confidence: 99%